FUNGSI AUDIT INTERNAL DAN PENGENDALIAN INTERNAL DALAM PELAKSANAAN GOOD CORPORATE GOVERNANCE (Studi pada Perusahaan SPBU di Kota Malang ) - Laela Purnamasari; Nur Hidayati; Moh. Amin (Universitas Islam Malang, 2020)
This survey was conducted to analyze the impact of internal auditors and internal controls on the implementation of good corporate governance. The sample in this survey was 55 Malang gas station employees. The analysis tool used is SPSS version 22 with multiple linear regression analysis methods. Based on the findings of the previous chapter, the results of internal auditors and internal controls can simultaneously influence the implementation of good corporate governance. In part, the internal auditor variable has a positive effect on good corporate governance practices. Internal control variables partially affect good corporate governance enforcementProposal Keywords: Quality Audit, Earning Response Coefficient (ERC) and Manufacturing Company